2010
DOI: 10.1016/j.jebdp.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Implementing Evidence-Based Clinical Guidelines: A Survey of Early Adopters

Abstract: Objective The purpose of this study is to identify barriers that early-adopting dentists perceive as common and challenging when implementing recommendations from evidence-based (EB) clinical guidelines. Method This is a cross-sectional study. Dentists who attended the 2008 Evidence-based Dentistry Champion Conference were eligible for inclusion. Forty-three dentists (34%) responded to a 22-item questionnaire administered online. Two investigators independently coded and categorized responses to open-ended i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(128 citation statements)
references
References 38 publications
7
117
1
Order By: Relevance
“…The most common barriers to implementation of early-adopting dentists are difficulty in changing current practice model, resistance and criticism from colleagues, and lack of trust in evidence or research [7].…”
Section: B) Factors Associated With the Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common barriers to implementation of early-adopting dentists are difficulty in changing current practice model, resistance and criticism from colleagues, and lack of trust in evidence or research [7].…”
Section: B) Factors Associated With the Patientmentioning
confidence: 99%
“…Unfortunately, just 32% of children aged 6 to 19 years have sealants. This may be due to the relatively slow translation of current biomedical science into dental practice [7].…”
Section: Introductionmentioning
confidence: 99%
“…48 This issue is at the heart of the expressed scepticism by many practitioners: one of the most common barriers to implementation of EBD is the lack of trust in evidence or research. 49 Carlsen and colleagues found that general practitioners' trust in guidelines is outweighed by their concerns with widespread guideline implementation -primarily because of differences between real patients and those portrayed in the guidelines. According to some professionals, guidelines…”
Section: Dentist Dissatisfactionmentioning
confidence: 99%
“…50 Other barriers to the EBD implementation are a lack of up-to-date evidence, a lack of clear answers to clinical questions, and contradictory information in the scientific literature. 49,51 Those flaws particularly affect dentistry since dental research funding is inferior to other medical fields where mortality/morbidity is higher. Also, instead of prescribing medication, the main interventions in dentistry involve complex manual manipulations (e.g.…”
Section: Dentist Dissatisfactionmentioning
confidence: 99%
“…[3] Antiretroviral treatment (ART), in the form of highly active anti retroviral therapy, consists of a combination of two nucleoside reverse transcriptase inhibitors (NRTIs) and a nonNRTI or a protease inhibitor. The South African (SA) 2004 antiretroviral (ARV) guidelines recommended a combination of stavudine (d4T) and lamivudine (3TC) as the NRTI backbone in the firstline regimen and a combination of zidovudine (AZT) and didanosine (DDI) as the backbone in the secondline regimen.…”
mentioning
confidence: 99%